Pelatihan Desain Grafis Menggunakan Aplikasi Canva dalam Mengasah Keterampilan Siswa-Siswi di MTS Wonosobo - Anisa Fitri Latifah; Fadila Sholaica Gunatria; Gina Mardiah; Harits Yahya Widodo; Laila Kurnia Astuti; Lulu' Ardiah 'Arifah; Mohammad Ridwan Widiarsa; Muhamad Fani; Safira Hasna Fatimah; Sylvia Rasyha Suci Amelia (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Graphic design training using the Canva application aims to enhance the skills of MTs Al-Muttaqin students in creating visual designs, particularly posters with the theme